EFFECT OF RUELLIA TUBEROSA L. LEAF NANOPARTICLES ON SEMINIFEROUS TUBULE DIAMETER AND GERMINAL EPITHELIUM THICKNESS IN DIABETIC RATS - Wijaya, Tania Anggreani; Pavita, Daffa Alice; Chrismonica, Yunia (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia that can cause various pathological changes in the human body and animals. Oxidative stress due to diabetes can lead to spermatogenesis disorders and increased cell apoptosis in the testes. Ruellia tuberosa L. leaf contain antioxidant compounds, such as saponins, carotenoids, flavonoids, and phenols, that can be used as free radical scavengers to reduce oxidative stress levels. The manufacture of Ruellia tuberosa L. leaf nanoparticles using the top-down method enhances pharmacological activity, particularly by facilitating cell wall penetration and improving the absorption of active substances in the body. This study employed a proper experimental design with a post-test-only control group model using Wistar rats as experimental animals. The treatment groups in this study included K- (control), K+ (diabetic control), P1 (exogenous long-acting insulin 1.80 IU/kg BW), P2 (Ruellia tuberosa L. leaf nanoparticles dose of 200 mg/kg BW), and P3 (Ruellia tuberosa L. leaf nanoparticles dose of 400 mg/kg BW). Testicular retrieval was performed 28 days after administration of Ruellia tuberosa L. leaf nanoparticles. Testicular histopathology was stained using Hematoxylin-Eosin staining and examined under a trinocular microscope at 100X magnification. Data on the diameter and thickness of the germinal epithelium were analyzed using the ANOVA test, followed by Duncan’s test. The results showed that administration of Ruellia tuberosa L. leaf nanoparticles at a dose of 400 mg/kg BW was an effective dose in increasing the diameter of the seminiferous tubules and the thickness of the germinal epithelium compared to Ruellia tuberosa L. leaf nanoparticles at a dose of 200 mg/kg BW and exogenous long-acting insulin 1.80 IU/kg BW